2011
DOI: 10.4061/2011/207230
|View full text |Cite
|
Sign up to set email alerts
|

Human Motor Neuron Progenitor Transplantation Leads to Endogenous Neuronal Sparing in 3 Models of Motor Neuron Loss

Abstract: Motor neuron loss is characteristic of many neurodegenerative disorders and results in rapid loss of muscle control, paralysis, and eventual death in severe cases. In order to investigate the neurotrophic effects of a motor neuron lineage graft, we transplanted human embryonic stem cell-derived motor neuron progenitors (hMNPs) and examined their histopathological effect in three animal models of motor neuron loss. Specifically, we transplanted hMNPs into rodent models of SMA (Δ7SMN), ALS (SOD1 G93A), and spina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 26 publications
(50 reference statements)
1
33
0
Order By: Relevance
“…Transplanted motor neurons may replace the lost MNs. Studies have shown that transplanted ESCs derived MNs supported the endogenous neurons survival through secretion of beneficial growth factors in the SCI model [27], spinal muscular atrophy (SMA) and Amyotrophic lateral sclerosis (ALS) model [28]. Transplanted OPCs may differentiate into mature oligodendrocytes to myelinate both ESCs derived MNs and constitutive MNs.…”
Section: Discussionmentioning
confidence: 99%
“…Transplanted motor neurons may replace the lost MNs. Studies have shown that transplanted ESCs derived MNs supported the endogenous neurons survival through secretion of beneficial growth factors in the SCI model [27], spinal muscular atrophy (SMA) and Amyotrophic lateral sclerosis (ALS) model [28]. Transplanted OPCs may differentiate into mature oligodendrocytes to myelinate both ESCs derived MNs and constitutive MNs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the intrathecal injection of neural stem cells in SMA mice has been proved to increase animal survival ameliorating their phenotype [42,43].…”
Section: Patients' Management and Therapeutic Perspectivesmentioning
confidence: 99%
“…Therefore, the primary aim of the present study was to explore the cytotoxicity of the 35-kDa and 26-kDa fragments, as well as the p.A315T and p.A382T mutants, against human embryonic stem (ES) cell-derived motor neurons. 13 RNA editing at the Q/R site of AMPA receptor subunit 2 (GluA2) mRNA is reportedly insufficient in the spinal motor neurons of sporadic ALS patients.…”
Section: Introductionmentioning
confidence: 99%